Peri-abortion contraceptive counseling: A systematic review of randomized controlled trials. - Patricia Gonzales-Huaman; Jose Ernesto Fernandez-Chinguel; Alvaro Taype-Rondan (PLoS ONE)
Objective To assess the effects of peri-abortion contraceptive counseling interventions. Methods We performed a systematic review of randomized controlled trials (RCTs) that compared the effect of different types of peri-abortion contraceptive counseling interventions and were published as original papers in scientific journals. The literature search was performed in June 2021 in PubMed, Central Cochrane Library (CENTRAL), Scopus, and Google Scholar; without restrictions in language or publication date. Two independent authors identified studies that met the inclusion and exclusion criteria and extracted the data. The risk of bias was assessed using the Cochrane tool, and evidence certainty was assessed using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology. Whenever possible, meta-analyses were performed. The protocol was registered at PROSPERO (CRD42020187354). Results Eleven RCTs were eligible for inclusion (published from 2004 to 2017), from which nine compared enhanced versus standard counseling. Pooled estimates showed that, compared to standard counseling, enhanced counseling was associated with a higher incidence of effective contraceptive use (>3 months) (relative risk [RR], 1.12; 95% confidence interval [CI], 1.09-1.16), although no significant difference was found in the incidence of long-acting reversible contraceptive use (RR, 1.25; 95% CI, 0.68-2.29), contraceptive uptake (RR, 1.06; 95% CI, 0.98-1.15), and obstetric event occurrence (RR, 0.91; 95% CI, 0.57-1.47). Certainty of evidence was very low for all outcomes. In addition, two studies compared contraceptive counseling provided by physicians versus that provided by non-physicians, which did not show significant differences. Conclusions Enhanced contraceptive counseling may favor effective contraceptive use but may not affect the rate of obstetric event occurrence. Also, the studies did not find a difference in the effects of counseling interventions given by different providers. Since evidence certainty was very low, future well-designed RCTs are needed to make informed decisions. Registration The study protocol was registered at PROSPERO (CRD42020187354).